2021
DOI: 10.7554/elife.70989
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis leads to lasting changes in phenotype and function of memory CD8 T cells

Abstract: The global health burden due to sepsis and the associated cytokine storm is substantial. While early intervention has improved survival during the cytokine storm, those that survive can enter a state of chronic immunoparalysis defined by transient lymphopenia and functional deficits of surviving cells. Memory CD8 T cells provide rapid cytolysis and cytokine production following re-encounter with their cognate antigen to promote long-term immunity, and CD8 T cell impairment due to sepsis can pre-dispose individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 86 publications
2
20
0
Order By: Relevance
“…10 Multiple cytokines, including IFN-γ, IL-2 and TNF-α, have been identified as key regulators in T-cell activation, with the ability to trigger T-cell activation response in a TCR-independent manner. 29 Studies have revealed that the transcriptional profile and chromatin accessibility are altered in memory T cells from sepsis survivors, leading to decreased T-cell cytokine secretion and reduced infection control, 30 which is consistent with our results. We found that the level of IL-2 released by memory CD8 + T cells and the level of IFN-γ released by memory CD4 + T cells of nonsurvivors were significantly decreased, which may abrogate the response of T cells to infection.…”
Section: Discussionsupporting
confidence: 91%
“…10 Multiple cytokines, including IFN-γ, IL-2 and TNF-α, have been identified as key regulators in T-cell activation, with the ability to trigger T-cell activation response in a TCR-independent manner. 29 Studies have revealed that the transcriptional profile and chromatin accessibility are altered in memory T cells from sepsis survivors, leading to decreased T-cell cytokine secretion and reduced infection control, 30 which is consistent with our results. We found that the level of IL-2 released by memory CD8 + T cells and the level of IFN-γ released by memory CD4 + T cells of nonsurvivors were significantly decreased, which may abrogate the response of T cells to infection.…”
Section: Discussionsupporting
confidence: 91%
“…The sepsis-induced changes in the composition of the memory CD8 T-cell pool and transcriptional landscape culminated in an altered T-cell function and reduced capacity to control L. monocytogenes infection. This may change the host’s capacity to respond to reinfection ( 29 ). In a prospective cohort study, B cells and follicular T cells were linked.…”
Section: Discussionmentioning
confidence: 99%
“…B cells are considered to have protective functions in sepsis, including antibody-dependent and non-dependent mechanisms ( Kelly-Scumpia et al, 2011 ). However, B cells of sepsis undergo massive apoptosis, and release PAMP and DAMP ( Hotchkiss et al, 2002 ; Jensen et al, 2021 ). Some researches found that serum IgM and IgG antibody concentrations are elevated under sepsis induction ( Nicolai et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%